A Practitioner's Review of Design Decisions Related to Equating and Linking with Small Samples (Commentary). Issue 1 (2nd January 2020) - Saiar, Amin
ABSTRACT: A commentary on the articles presented in this issue is provided that focuses on a practitioner's perspective on equating and linking with small samples. A review of each article's design and outcomes is followed by the practical implications when implementing the researched study elements and the guidance offered by the authors. Inter-relationships among the variables of interest presented in the articles (measurement model, equating procedure, anchor item selection, item parameter drift, and data collection/retention processes) are examined and some attempts at prioritization are provided. Key take-aways are offered, which include a careful approach to anchor item selection and form assembly, usage of empirical data over SME judgments when determining equivalence, and thoughtful consideration of the many permutations of design decisions prior to implementation.